PENGARUH KLASIFIKASI USAHA KECIL TERHADAP KREDIT MODAL KERJA PADA PT.BPRS NIAGA MADANI CABANG MAKASSAR - Fitriani Latief (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
Classification of Small Business is a grouping of some of the characteristics of entrepreneurs are small, ranging from income, entrepreneurial skills, and motivation to grow, which in the classification of small business is divided into 4 groups: Livehood Activities, Micro Enterprise, Small Dynamic Enterprise, Fast Moving Enterprise. Working capital is the capital that is used to perform the operations of the company as invested in liquid assets or short-term assets. This study uses analysis test and multiple linear description of the entire Account Officer PT. SRB Commerce Madani Branch Makassar. Results obtained F test at page 53 paragraph 4 shows simultaneously variable Livehood Activities, and Micro Enterprise significant effect on working capital loans. Then partially or t test on page 54, paragraph 3 shows that partially or individual all independent variables namely Livehood actvities and Micro Enterprise significant effect on working capital loans.